Breeding value predictive accuracy for scarcely recorded traits in a Eucalyptus grandis breeding population using genomic selection and data on predictor traits - Jurcic, Esteban Javier; Villalba, Pamela Victoria; Dutour, Joaquín; Centurión, Carmelo; Munilla, Sebastián; Cappa, Eduardo Pablo (Springer, 2023)
Genomic selection methods are particularly useful for traits that are difcult or expensive to measure. We investigated the impact of using predictor growth traits and/or genomic information to increase the breeding value (BV) predictive accuracies for target scarcely recorded wood quality traits in an open-pollinated Eucalyptus grandis population. The performance of single- and multiple-trait single-step genomic best linear unbiased prediction and conventional pedigree-based models were compared in terms of the predictive accuracies (PA) of estimated BV for the target traits. We also derived the contributions of the BV for candidate trees to better understand our results. The inclusion of predictor traits in both, the training and the validation sets, together with genomic information, improved the PA (up to 17.7%) for pulp yield and cellulose. However, signifcant improvements in PA were not observed when predictor traits were recorded only in the training set or when the impact of genomic information alone was assessed. Changes in the PA were explained by the variations in the maternal contributions, contribution/s from all the predictor/s trait/s, and from genotyped trees. We conclude that there is not a “uni versal” rule regarding the use of genomic information and records on predictor traits. However, assessing the contributions to the BV of validation trees may help to better design how to beneft from predictor traits in forest tree breeding.